2022
DOI: 10.1093/cercor/bhac051
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum and cognition: further evidence for its role in language control

Abstract: The cognitive function of the human cerebellum could be characterized as enigmatic. However, researchers have attempted to detail the comprehensive role of the cerebellum in several cognitive processes in recent years. Here, using functional magnetic resonance imaging (fMRI) and transcranial direct current stimulation (tDCS), we revealed different functions of bilateral cerebellar lobules in bilingual language production. Specifically, brain activation showed the bilateral posterolateral cerebellum was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Additional regions included those involved in motor, behavioral, cognitive, and language control; primary visual processing and interhemispheric communication (cerebellum; primary visual cortex, corpus callosum) [68][69][70][71][72][73][74][75] . Morphometrically, we observed alterations in regional volume, thickness, and surface area relative to global measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional regions included those involved in motor, behavioral, cognitive, and language control; primary visual processing and interhemispheric communication (cerebellum; primary visual cortex, corpus callosum) [68][69][70][71][72][73][74][75] . Morphometrically, we observed alterations in regional volume, thickness, and surface area relative to global measures.…”
Section: Discussionmentioning
confidence: 99%
“…Identified brain regions are mainly involved in receptive and expressive language, social and face processing (bank STS, middle temporal, superior temporal, medial orbitofrontal, caudal anterior cingulate, posterior cingulate, pars opercularis, caudal middle frontal) 57-67 . Additional regions included those involved in motor, behavioral, cognitive, and language control; primary visual processing and interhemispheric communication (cerebellum; primary visual cortex, corpus callosum) 68-75 . Morphometrically, we observed alterations in regional volume, thickness, and surface area relative to global measures.…”
Section: Discussionmentioning
confidence: 99%
“…According to GC-MS results, substances with matching values less than 70 were filtered, and the retention indexes were calculated based on the n-alkanes using the Kovats index. The olfactory components of PEO were identified in Table 1, with a total of 59 compounds, including terpenes (14), alcohols (11), aldehydes (4), ketones (10), acids (2), esters (7), phenols (2), and other organic compounds (9). Alcohols and terpenes account for 49.82 percent of the total content.…”
Section: Volatile Chemicals Comprising Peomentioning
confidence: 99%
“…Aromatic compounds in EOs can affect the nervous system via smell. The aroma of EOs activates synaptic transmission to the central nervous system, and the signal input eventually rises to several brain areas responsible for olfactory perception, autonomic balance, and other advanced brain functions, thereby affecting the body and the mind [11,12]. Most past EEG studies of odour effects have shown that alpha activity can be increased by taking several EOs, such as lavender, sandalwood, and chamomile oils.…”
Section: Introductionmentioning
confidence: 99%
“…These are significant findings. The cerebellum is chiefly associated with motor skills, visualmotor coordination, and balance; however, numerous developmental dyslexia theories have shown that decreased cerebellocortical connectivity and anomalies in the cerebellum structure contribute to language development [2]. Similarly, the cerebellum has been speculated to have a role in cognitive capabilities [2], but the international consensus from experts remains highly inferential [3].…”
mentioning
confidence: 99%